ANALISIS SERTA PERENCANAAN PERTUMBUHAN EKONOMI DAN INVESTASI DI SUMATERA BARAT - Yola Sastri, Ridha; Aimon, Hasdi; Syofyan, efrizal (Program Studi Magister Ilmu Ekonomi, 2013)
This article focused on analyze (1) Effect of consumption, invesment, government spending and net export on the economics growth in West Sumatera. (2) Effect of economics growth, interest rate and money supply on the invesment in West Sumatera. (3) Planning ofÂ the economics growth and investment about 2013-2017. Data used time series of (I year kuartal 2001â€“ IV year kuartal 2010). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS). The result of research concludes that (1) the consumption have a significant and positive impact on the economics growth, invesment have significant and positive impact on the economics growth, government spending rates significantly and positive on the economics growth and net export have a significant and positive impact on the economics growth in West Sumatera. (2) the economics growth have a significant and positive impact on the invesment, interest rate have a significant and positive impact on the invesment and money supply have a significant and positive impact on the invesment in West Sumatera.(3)Prospect of output and employment inj West Sumatera 2013-2015 is positive. Keywords : Economics Growth, Invesment, Consumption, Government Spending, Net Export, Interest Rate, Money Supply